True romance [videorecording (DVD)] - Zimmer, Hans (Warner Home Video, 2007)
The story of two unlikely lovers who find themselves in possession of a suitcase full of valuable mob contraband which they plan to take from Detroit to Los Angeles, sell, and begin a new life.